2022
DOI: 10.3389/fgene.2022.1036156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of susceptibility modules and hub genes of osteoarthritis by WGCNA analysis

Abstract: Osteoarthritis (OA) is a major cause of pain, disability, and social burden in the elderly throughout the world. Although many studies focused on the molecular mechanism of OA, its etiology remains unclear. Therefore, more biomarkers need to be explored to help early diagnosis, clinical outcome measurement, and new therapeutic target development. Our study aimed to retrieve the potential hub genes of osteoarthritis (OA) by weighted gene co-expression network analysis (WGCNA) and assess their clinical utility f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…WGCNA is a systems biology method used to construct gene co-expression networks and identify gene modules associated with specific diseases or biological processes. It utilizes gene expression data to calculate the correlation between genes and cluster highly correlated genes into modules, revealing gene regulatory networks and key regulatory genes [ 33 ]. Previous studies have employed WGCNA to analyze gene expression data, identify gene modules related to OA [ 33 , 34 ], and perform functional enrichment analysis to understand the biological mechanisms of OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WGCNA is a systems biology method used to construct gene co-expression networks and identify gene modules associated with specific diseases or biological processes. It utilizes gene expression data to calculate the correlation between genes and cluster highly correlated genes into modules, revealing gene regulatory networks and key regulatory genes [ 33 ]. Previous studies have employed WGCNA to analyze gene expression data, identify gene modules related to OA [ 33 , 34 ], and perform functional enrichment analysis to understand the biological mechanisms of OA.…”
Section: Discussionmentioning
confidence: 99%
“…It utilizes gene expression data to calculate the correlation between genes and cluster highly correlated genes into modules, revealing gene regulatory networks and key regulatory genes [ 33 ]. Previous studies have employed WGCNA to analyze gene expression data, identify gene modules related to OA [ 33 , 34 ], and perform functional enrichment analysis to understand the biological mechanisms of OA. Machine learning algorithms and gene expression data have been integrated to identify potential diagnostic biomarkers with predictive value for OA [ 26 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formyl peptide receptors (FPRs) are G protein-coupled receptors, and formyl peptides act on FPR1 and FPR2, transducing chemotactic signals in phagocytes, and mediating host-defense as well as inflammatory responses including cell adhesion, directed migration, granule release, and superoxide production ( He and Ye, 2017 ). It has been shown that the expression of FPR2 in the KD group is significantly higher than that in the healthy control group, and the increase in FPR2 levels may be involved in the regulation of the in vivo balance of the immune system ( Wang Y et al, 2022 ). Hematopoietic cell kinase (HCK) is a member of the Src family of non-receptor tyrosine kinases, which plays a critical role in neutrophil phagocytosis ( Cheng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…P value < 0.05 and |log2 FC (fold change)| > 1 were set as the cutoff for DEGs. [ 15 ] Subsequently, we visualized the DEGs by a heatmap and a volcano map, respectively. Finally we overlapped the DEGs of CD and EMT in order to obtain common genes.…”
Section: Methodsmentioning
confidence: 99%